Analytical computation of arm inductor for minimizing MMC circulating current using passive method - Aslam, Amna; Raza, Muhammad (Center of Biomass & Renewable Energy (CBIORE), 2025)
The study of circulating currents in modular multilevel converters is vital for improving their efficiency and reliability. The circulating current may arise from capacitor voltage unbalancing, modulation imperfections, load variations, and transient conditions. Such currents typically induce distortions in arm currents, exhibiting second-order harmonics that lead to power losses and negatively impact the ratings of converter components as well as the amplitudes of capacitor voltage ripples. Despite ongoing research, effective strategies to mitigate circulating currents are limited. This paper aims to systematically address this issue by selecting key design parameters specifically arm inductance and capacitor values, to suppress circulating currents. The methodology incorporates harmonic analysis and instantaneous power theory to derive expressions for arm inductance. Initial modelling includes common mode and differential mode analyses, leading to an examination of harmonic content. Analysis reveals that the selection of the arm inductor value is mainly influenced by the second-order harmonic component, whereas the capacitor value is determined by the fundamental harmonic component. By adopting this methodology, the boundary limit for arm inductor selection can be determined. This article proposes a novel expression for arm inductor selection. The proposed expression mainly depends on factors such as load, submodule capacitor voltages, submodule capacitor, and differential current. By selecting an appropriate inductor value based on converter-rated parameters, circulating current within the system can be effectively suppressed. The methodology offers a practical framework for arm inductor selection. Simulation results validation shows strong alignment with analytical results with the error margin of less than 1%, hereby the MMC parameter can be determined with better accuracy through analytic method.